2018
DOI: 10.1128/aac.00927-18
|View full text |Cite
|
Sign up to set email alerts
|

Tet38 Efflux Pump Contributes to Fosfomycin Resistance in Staphylococcus aureus

Abstract: Fosfomycin inhibits MurA following uptake by the GlpT transporter of glycerol-3-phosphate in In, plasmid overexpression of the Tet38 efflux pump and a mutant resulted in increased MICs and decreased accumulation of fosfomycin, with MICs affected by glycerol-3-phosphate. In contrast, a mutant had a lower MIC and increased accumulation of fosfomycin, suggesting that Tet38 acts as an efflux transporter of fosfomycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Recent studies have shown that the tet38 gene exerts a specific effect on fosfomycin resistance. According to the study by Truong-Bolduc, the overexpression of tet38 resulted in a fourfold increase in the MIC of fosfomycin compared with that of the parent strain ( Truong-Bolduc et al, 2018 ). The results of the current study showed that the expression of the tet38 efflux pump gene in fosfomycin-resistant strains JP3212, JP3535, JP3592, and JP3600 was significantly higher than that in the control strain ATCC29213 and the susceptible strains ( P = 0.007, P = 0.002, P < 0.001, P < 0.001, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the tet38 gene exerts a specific effect on fosfomycin resistance. According to the study by Truong-Bolduc, the overexpression of tet38 resulted in a fourfold increase in the MIC of fosfomycin compared with that of the parent strain ( Truong-Bolduc et al, 2018 ). The results of the current study showed that the expression of the tet38 efflux pump gene in fosfomycin-resistant strains JP3212, JP3535, JP3592, and JP3600 was significantly higher than that in the control strain ATCC29213 and the susceptible strains ( P = 0.007, P = 0.002, P < 0.001, P < 0.001, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the MurA target enzyme and transporters (GlpT and UhpT) have been shown to be responsible for fosfomycin resistance ( Michalopoulos et al, 2011 ). Additionally, the overexpression of target enzymes, MurA and Tet38 efflux pump, also contributes to fosfomycin resistance in S. aureus ( Truong-Bolduc et al, 2018 ). Notably, there are no reports yet suggesting that fosfomycin can stimulate the expression of the efflux pump gene and mediate drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Tet38 functions as a broad-spectrum membrane transporter in S. aureus, and its substrate spectrum includes chemically unrelated compounds (palmitoleic acid and glycerol-3-phosphate) and antibiotics (tetracycline and fosfomycin). Tet38 also contributes to S. aureus invasion of A549 epithelial cells (14,20,21,23), but there is limited understanding of the mechanism by which it facilitates bacterial internalization into host cells. Using antibodies against host cell receptors CD36 and TLR-2 to block the entrance of S. aureus, we found that a blockage with anti-CD36 antibody was effective only in the presence of Tet38, and anti-TLR-2 antibody had an additional 2-fold effect on internalization of the tet38 mutant QT7.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that the Tet38 efflux pump, which extrudes diverse substrates such as tetracycline, fosfomycin, free fatty acids, and glycerol-3-phosphate, is involved in the internalization of S. aureus by A549 epithelial cells, as evidenced by a 5-fold reduction in the recovery of a tet38 mutant after A549 cell invasion (13,14). Treatment of A549 cells with anti-CD36 antibody reduced binding of wild-type cells 2-fold but had no effect on the tet38 mutant, suggesting that Tet38 interacted with CD36 in host cell invasion (13).…”
mentioning
confidence: 99%
“…Ponieważ spektrum substratowe systemów Mex obejmuje wiele różnych klas substancji przeciwbakteryjnych, ich podwyższona synteza może przyczyniać się do występowania wielooporności u Pseudomonas. Fosfomycyna nie stanowi substratu dla systemów typu Mex, natomiast dowiedziono, że może być usuwana z komórek bakteryjnych przy udziale pompy Tet38 [60,94].…”
Section: Czynne Usuwanie Cząsteczek Substancji Przeciwbakteryjnejunclassified